Luminescent metal nanoclusters: controlled synthesis and functional applications - Sun, Hong-Tao (Taylor & Francis, 2013)
Luminescent metal nanoclusters that consist of only several, to tens of, metal atoms and which possess sizes comparable to the Fermi wavelength of electrons have recently attracted significant attention. This new class of luminescent materials not only provides the missing link between atomic and nanoparticle behaviors in metals but also they present abundant novel information for the development of new applicable material systems to meet urgent needs in many areas (such as ultrasensitive sensors for heavy metals, bioimaging, as well as information technology) mainly because of their attractive characteristics, including ultra-small size, good dispersibility, excellent biocompatibility and photostability. In this review, we summarize recent advances in the controlled synthesis and application of luminescent metal nanoclusters, with a particular emphasis on Pt, Mo, Bi and alloy clusters. We also speculate on their future and discuss potential developments for their use in sensors, bioimaging and energy harvesting and conversion.